2022
DOI: 10.1002/jsfa.12048
|View full text |Cite
|
Sign up to set email alerts
|

Effects of selenium application concentration, period and method on the selenium content and grain yield of Tartary buckwheat of different varieties

Abstract: BACKGROUND As a potential selenium‐enriched crop, it is of great significance to study the selenium application of Tartary buckwheat. Therefore, to study the effects of selenium application concentration, variety, selenium application period and method on the grain selenium content and yield of Tartary buckwheat, an orthogonal experimental design was used to carry out field experiments in the Jinzhong and Northwest Shanxi ecological regions at the same time. Heifeng 1 and Jinqiao 2 were applied at the branchin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 37 publications
1
1
0
Order By: Relevance
“…Therefore, the treatment used in the experiments did not negatively affect seedling growth. Our results are consistent with those from previous reports in that selenium within a certain concentration range is safe and does not have a negative impact on buckwheat growth (Liu et al, 2022;Ma et al, 2020;Song et al, 2019). In addition to the concentration of selenium, plant biomass and growth characteristics are also associated with selenium speciation and the plant species and variety (Jiang et al, 2018;Rao et al, 2021).…”
Section: Selenium Concentration and Sprout Growthsupporting
confidence: 93%
See 1 more Smart Citation
“…Therefore, the treatment used in the experiments did not negatively affect seedling growth. Our results are consistent with those from previous reports in that selenium within a certain concentration range is safe and does not have a negative impact on buckwheat growth (Liu et al, 2022;Ma et al, 2020;Song et al, 2019). In addition to the concentration of selenium, plant biomass and growth characteristics are also associated with selenium speciation and the plant species and variety (Jiang et al, 2018;Rao et al, 2021).…”
Section: Selenium Concentration and Sprout Growthsupporting
confidence: 93%
“…Inorganic selenium dramatically affects plant nutritional quality, growth and development (Malagoli et al, 2015). In buckwheat, a suitable concentration of selenium greatly improves the grain quality and yield, and soil with an appropriate concentration of Se improved the contents of crude protein, fat, and flavonoids in seeds (Cao et al, 2021;Liu et al, 2022). Previous studies have suggested that buckwheat is highly tolerant to selenium accumulation, which makes it suitable for development of selenium-enriched food products (Golob et al, 2015;Golob et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…These findings corroborate the varied potential outcomes of Se fertilization on agricultural yields, which can manifest as increased yield, 7,31 no effect on yield, 9 or a reduction in yield. 29…”
Section: Impact Of Se Fertilization On Se Content and Yieldmentioning
confidence: 99%
“…26 For Tartary buckwheat, yields initially increase and then decrease with both foliar and soil Se fertilization within the range of 0 to 28 g ha −1 . 29 In addition, soil Se fertilization within specific application rates (30 g ha −1 to 40 kg ha −1 ) can increase crop yields and mitigate the accumulation of heavy metals such as arsenic and cadmium in soils. 30,31 Thus, assessing the relationship between Se fertilization rates and the Se content and yields of different agricultural crops is necessary because approximately 800 million people are facing severe food shortages worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Se biofortification agronomic strategies can be categorized into Se fertilizer strategies and agronomic management strategies (Figure 1). In this section, we initially summarize the crucial role of Se fertilizer strategies, including how to adjust the type [36][37][38] and dosage of Se fertilizers [39,40], and the application site [32,41] and timing of Se [42,43]. Subsequently, we consolidate and discuss the impacts of agronomic management strategies on Se biofortification, encompassing crop rotation [44][45][46] and intercropping [47][48][49] and soil [50][51][52] and water management [53][54][55], as well as microbial inoculation [56][57][58].…”
Section: Agronomic Strategies For Se Biofortificationmentioning
confidence: 99%